Cardiac diffusion-weighted and tensor imaging: A consensus statement from the special interest group of the Society for Cardiovascular Magnetic Resonance - Erica Dall’Armellina; Daniel B. Ennis; Leon Axel; Pierre Croisille; Pedro F. Ferreira; Alexander Gotschy; David Lohr; Kevin Moulin; Christopher T. Nguyen; Sonja Nielles-Vallespin; William Romero; Andrew D. Scott; et al. (Journal of Cardiovascular Magnetic Resonance)
Thanks to recent developments in cardiovascular magnetic resonance (CMR), cardiac diffusion-weighted magnetic resonance is fast emerging in a range of clinical applications. Cardiac diffusion-weighted imaging (cDWI) and diffusion tensor imaging (cDTI) now enable investigators and clinicians to assess and quantify the tridimensional microstructure of the heart. Free-contrast DWI is uniquely sensitized to the presence and displacement of water molecules within the myocardial tissue, including the intracellular, extracellular, and intravascular spaces. CMR can determine changes in microstructure by quantifying: a) mean diffusivity (MD)—measuring the magnitude of diffusion; b) fractional anisotropy (FA)—specifying the directionality of diffusion; c) helix angle (HA) and transverse angle (TA)—indicating the orientation of the cardiomyocytes; d) absolute sheetlet angle (E2A) and E2A mobility—measuring the alignment and systolic-diastolic mobility of the sheetlets, respectively.This document provides recommendations for both clinical and research cDWI and cDTI, based on published evidence when available and expert consensus when not. It introduces the cardiac microstructure focusing on the cardiomyocytes and their role in cardiac physiology and pathophysiology. It highlights methods, observations, and recommendations in terminology, acquisition schemes, postprocessing pipelines, data analysis, and interpretation of the different biomarkers. Despite the ongoing challenges discussed in the document and the need for ongoing technical improvements, it is clear that cDTI is indeed feasible, can be accurately and reproducibly performed and, most importantly, can provide unique insights into myocardial pathophysiology.